The effects of first-line pharmacological treatments for reproductive outcomes in infertile women with PCOS: a systematic review and network meta-analysis - Ge Peng; Zhe Yan; Yuqi Liu; Juan Li; Jinfang Ma; Nanwei Tong; Yan Wang (BMC, 2023)
Abstract Background Polycystic ovarian syndrome (PCOS) is one of the most common causes of infertility in reproductive-age women. However, the efficacy and optimal therapeutic strategy for reproductive outcomes are still under debate. We conducted a systematic review and network meta-analysis to compare the efficacy of different first-line pharmacological therapies in terms of reproductive outcomes for women with PCOS and infertility. Methods A systematic retrieval of databases was conducted, and randomized clinical trials (RCTs) of pharmacological interventions for infertile PCOS women were included. The primary outcomes were clinical pregnancy and live birth, and the secondary outcomes were miscarriage, ectopic pregnancy and multiple pregnancy. A network meta-analysis based on a Bayesian model was performed to compare the effects of the pharmacological strategies. Results A total of 27 RCTs with 12 interventions were included, and all therapies tended to increase clinical pregnancy, especially pioglitazone (PIO) (log OR 3.14, 95% CI 1.56 ~ 4.70, moderate confidence), clomiphene citrate (CC) + exenatide (EXE) (2.96, 1.07 ~ 4.82, moderate confidence) and CC + metformin (MET) + PIO (2.82, 0.99 ~ 4.60, moderate confidence). Moreover, CC + MET + PIO (2.8, -0.25 ~ 6.06, very low confidence) could increase live birth most when compared to placebo, even without a significant difference. For secondary outcomes, PIO showed a tendency to increase miscarriage (1.44, -1.69 ~ 5.28, very low confidence). MET (-11.25, -33.7 ~ 0.57, low confidence) and LZ + MET (-10.44, -59.56 ~ 42.11, very low confidence) were beneficial for decreasing ectopic pregnancy. MET (0.07, -4.26 ~ 4.34, low confidence) showed a neutral effect in multiple pregnancy. Subgroup analysis demonstrated no significant difference between these medications and placebo in obese participants. Conclusions Most first-line pharmacological treatments were effective in improving clinical pregnancy. CC + MET + PIO should be recommended as the optimal therapeutic strategy to improve pregnancy outcomes. However, none of the above treatments had a beneficial effect on clinical pregnancy in obese PCOS. Trial registration CRD42020183541; 05 July 2020